STUDI PEMANFAATAN BERSAMA JARINGAN TRANSMISI PADA SISTEM TRANSMISI JAWA-BALI - , TAUFIQ INDRAPUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The electricity demand in Indonesia has increased rapidly in recent years. To serve the growing electricity demand, an additional generating capacity should be required. From that capacity there is unallocated project where developers and financial supports has not been established. To cover these unallocated additional capacity required, there are an opportunity for the third party non-IPP to participate in development of power generation through power wheeling. These concept of power wheeling is in developing stage of being implemented in Indonesia, especially in Java-Bali transmission system. This paper elaborates the feasibility analysis of several transmission cost allocation methods to be implemented on electricity wheeling in Java-Bali transmission system. From the discussion, it is known that any method for determining the cost of the transmission network has advantages and disadvantages in the wheeling of electric power applications in the Java-Bali transmission system.